PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATERI STRUKTUR ATOM DENGAN MENGUNAKAN MODEL STUDENT TEAMS ACHIVEMENT DIVISION (STAD) DI KELAS X-MIA.D SMA NEGERI 1 LAWANG KIDUL - Wiyoko (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
This study is a classroom action research that aims to improve students’ learning outcomes by using STAD (Student Teams Achievement Division) model. The subjects of this study are students of SMA Negeri 1 Lawang Kidul X-MIA.D year 2017/2018 as many as 27 students. This research took place in two cycles, data analysis using comparative descriptive analysis that is by comparing test value between cycles. The result of the research showed that there was an increase in the number of students’ learning achievement in the material of atomic structure from 59.26% (16 people) in the first cycle to 85.19% (23 people) in the second cycle. Likewise the activity of learners in the learning process increased from 4.83 to 7.93. In the group awards also experienced an increase in the average score from 19 to 23.